Proximate and Mineral Composition of Atlantic Mackerel (Scomber scombrus) and Atlantic Horse Mackerel (Trachurus trachurus) - Sanni, Joseph Adaviruku; Sanni, Grace Omayoza; Awoniyi, Rufus Ranmilowo; Osanyinlusi, Remi; Richards, Yvonne Ego (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Atlantic mackerel (Scomber scombrus) and Atlantic horse mackerel (Trachurus trachurus), locally known as kote, are fishery species consumed in Nigeria due to their high nutritional values. This research determined the nutritional composition of the local dried fish, Scomber scombrus and Trachurus trachurus. Results for Scomber scombrus shows the mean value of the moisture, ash, crude fat, crude fiber, and crude protein contents in percent (%) as: 5.26±0.00, 5.20±0.10, 35.60±0.00, 2.90±0.10 and 46.30±0.01 respectively. For Trachurus trachurus, the moisture, ash, crude fat, crude fiber, and crude protein contents in percent (%) were 9.52±0.00, 32.26±0.01, 24.14±0.00, 11.91±0.85 and 40.95±0.00 respectively. The mineral composition of Scomber scombrus was as follows: Sodium (Na) had the highest mineral composition with 78.90 mg/100g, followed by magnesium (Mg) with 15.90 mg/100g, manganese (Mn) with 0.86 mg/100g, zinc (Zn) with 0.282 mg/100g, and iron (Fe) with 0.10 mg/100g. Trachurus trachurus has magnesium (Mg) at 27.00 mg/100g as its highest mineral composition, followed by sodium (Na) at 22.50 mg/100g, zinc (Zn), iron (Fe) at 0.17 mg/100g, and manganese (Mn) at 0.09 mg/100g. It is concluded from the study, that Scomber scombrus and Trachurus trachurus are good sources of essential nitrates, fat, proteins containing essential amino acids, and other micronutrients that are beneficial to human health.